Tooth Numbering System in Saudi Arabia: Survey - Sulieman S. Al-Johany (Saudi Dental Journal)
Objective: There were four aims of the current study: (1) to find the most commonly used Tooth Numbering System (TNS) in Saudi Arabia in both academic and non-academic institutions, (2) to identify the most commonly taught TNS in dental colleges, (3) to understand the reasons why dental practitioners prefer to use a specific TNS, and (4) the consequences of using more than one TNS. Materials and method: Between May 2014 and May 2015, a self-administered questionnaire containing 21 questions was randomly distributed to 121 individuals (20 deans of dental colleges and 101 heads of governmental dental centers). Results: The most commonly used TNS is the Fédération Dentaire Internationale (FDI) TNS for both primary and permanent dentitions in both academic and non-academic institutions, followed by the Palmer TNS and then the Universal TNS. Conclusion: The FDI TNS proved to be the most taught TNS in dental colleges in Saudi Arabia. It is advised that the FDI TNS be implemented as a unified system in Saudi Arabia due to the advantages of this particular TNS and the benefits of using one single TNS. Keywords: Tooth Numbering System, FDI, Palmer, Universal, Academic, Saudi Arabia